Investigation of the influence of hypoxic – hypercapnic trining on respiratori functionof kaznu named by al-Farabi (Eurasian Journal of Ecology, 2016)
Investigated the functional state of the external respiration students not involved in hypoxic-hypercapnic Training at rest. Physiological indices of external respiration students at rest was determined on the basis of adaptive capacity. It is known that under the influence of systematic dyhatelnyh exercise increased reserve capacity of the organism. Students engaged in hypoxic-hypercapnicurpazhneniyami, compared to students not involved in hypoxic-hypercapnic exercises indicators above. However, according to our resulting research revealed satisfactory adaptation capabilities of external respiration students engaged and involved in hypoxic-hypercapnic exercises at rest.
Keywords: external respiration; respiratory rate; respiratory volume; inspiratory reserve volume; vital capacity; minute ventilation; hypoxic-hypercapnic training.